A quantum chemical study on the effect of titanium dioxide modification with non-metals on its spectral characteristics - O. V. Smirnova; A. G. Grebenyuk; V. V. Lobanov (Хімія, фізика та технологія поверхні, 2020)
The experimental results obtained in the study on the possibility of sensitizing titanium dioxide (polymorphic anatase phase) to the visible region of the spectrum by doping and co-doping with impurities of non-metals in order to create effective photocatalysts for the decomposition of organic compounds have been analyzed.